Embryonic Fibroblasts Promote Antitumor Cytotoxic Effects of CD8+ T Cells - Qin, Yingyu; Shin, Jung Hoon; Yoon, Jeong-Ho; Park, Se-Ho (Frontiers in Immunology, 2018)
Adoptive CD8+ T cell therapy has emerged as an important modality for the treatment of cancers. However, the significant drawback of transfused T cells is their poor survival and functionality in response to tumors. To overcome this limitation, an important consideration is exploring a culture condition to generate superior antitumor cytotoxic T lymphocytes (CTLs) for adoptive therapy. Here, we provide a novel approach to generate potent CTL clones in mouse embryonic fibroblast-conditioned medium (MEF-CM). We found CTLs derived with MEF-CM have higher potential in long term persistence in tumor bearing and non- tumor bearing mice. Importantly, adoptive transfer of MEF-CM cultured CTLs dramatically regressed tumor growth and prolonged mice survival. Characterization of MEF-CM cultured CTLs (effector molecules, phenotypes, and transcription factors) suggests that MEF-CM enhances the effector functions of CD8+ T cells in part by the up-regulation of the T-box transcription factor eomesodermin. Consequently, MEF-CM enhances the intrinsic qualities of effector CD8+ T cells to augment antitumor immunity.